The new attenuated strain of Mycobacterium tuberculosis BN. Characteristics and vaccine properties - B. V. Nikonenko; T. L. Аzhikina; A. S. Grigorov; I. A. Linge; N. N. Logunova; S. I. Kayukova (Туберкулез и болезни лёгких, 2021)
The objective of the study: to obtain a live attenuated strain and investigate its properties by multiple cultures of the virulent strain of Mycobacterium tuberculosis H37Rv.Subjects and Methods. The original virulent strain H37Rv was subcultured 70 times in 7H9 liquid medium. Genetic properties of the new strain, degree of avirulence, and vaccine properties were studied.Results. Mycobacteria of the new strain MtbBN lost their virulence to inbred mice. Eight mutations were identiﬁed by whole genome sequencing: single nucleotide insertions and deletions (in/del) distinguishing the MtbBN and H37Rv strains. The MtbBN strain demonstrated vaccine potential at the BCG level. Additionally, in some genetic models, the attenuated strain was highly eﬀective in protecting inbred mice when infected with Mtb H37Rv as opposed to BCG.